Evolving Coagency between Artists and AI in the Spatial Cocreative Process of Artmaking - Nordström Paulina; Lundman Riina; Hautala Johanna (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
This article applies theoretical and empirical discussions of emerging human and digital technology relations to our interest in collaborative artist-artificial intelligence (AI) artmaking processes. Thus far, the theoretical focus has largely been on mediating (code) and merged (cyborg) human-technology relations, with mutual (coagency) relations yet to be adequately explored. To address this, we nuance the theoretical discussion and extend the empirical research, analyzing the spatial cocreative artmaking process through video interviews with eighteen Finnish artists using AI. Drawing on the work of Barad, we regard humans and AI as fundamentally entwined, receiving their agencies through intra-action. Building on this, we demonstrate how the agencies of artists and AI emerge and mutually evolve across three stages of the creative process: (1) coding and data, (2) learning and training, and (3) curating the outcome. Thus, through our empirical research on how artist and AI create new material and meaningful artworlds, we are able to nuance understanding of coagency as a spatial process.
Key Words: agency, art, artificial intelligence, cocreativity, digital geographies.